(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2024)
Derived from broader research and using Marxism, as evidenced in the writings of Poulantzas (1980, 1981, 2019), as the epistemological reference, this text presents discussions about the neoliberal facets that guide the provision of Secondary Education in Brazil, in order to clarify whom education at this level has served. To this end, based on bibliographic and documentary research, discussions on “power blocs” and “fractions of the bourgeoisie” are presented, aiming to indicate the structuring of neoliberalism in Brazil and its consequent influence on education policies for Secondary Education across different governments (1994-2019). In the end, it is indicated that the governments of the period are not identical, but there are more points of commonality than points of differences among them. Therefore, it is emphasized that, given the current political context, it is crucial for these similarities to be clarified. Keywords: Neoliberalism. Education. Education policies. Secondary Education.